The effect of milk on recovery from repeated sprinting and jumping in female team-sport athletes - Rankin, P.; Landy, A.; Stevenson, E.; Cockburn, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Research has shown that consumption of milk post-eccentric exercise can attenuate the effects of exercise-induced muscle damage (EIMD) in team-sport athletes. However, these studies evoked damage using an intense eccentric protocol quite different to the exercise stress experienced by athletes during and after team sport training or competition. The aim of this study was to examine the effects of post-exercise milk consumption on recovery from activities that simulate those of team sport participation.